Mechanism of Saving Activity and Community Business Administration for Decreasing Household Debt - Dampitakse, Kusuma; Bualai, Hiang (RMUTT GLOBAL BUSINESS ACCOUNTING AND FINANCE REVIEW, 2017)
The purpose of the research project entitled “The Mechanism of Saving Activity and Community Business Administration for Decreasing Household Debt” was to investigate the pattern and guideline on household debt management by using the mechanism of saving, community business administration, and household financial management which was beneficial efficiently and sustainably. The research methodology emphasized on qualitative method comprised participatory observation, in-depth interview, and workshop. Furthermore, the quantitative method was also conducted by surveying household debt. The research results revealed that the members of saving groups saved their money based on five moral principles consisting of honesty, devotion, responsibility, sympathy, and trustworthiness. In addition to, they needed to create the source of community fund for consumption loan and household investment with lower interest rate. The process of household debt management began with saving and borrowing their loan for consumption and investment. They developed the discipline of saving and learned to manage their money for decreasing their debt. Moreover, they also linked the saving activities to expand their saving network to community enterprise in order to produce, for instance, drinking water, dishwashing liquid, and paper flower sold to members and people in the community at low prices to decrease their expenses. Nevertheless, the saving activity network was also expanded to provide social welfare to the members and people in the community.